2022
DOI: 10.1128/spectrum.00759-22
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Mediates the Protective Effects of Traditional Chinese Medicine Formula Qiong-Yu-Gao against Cisplatin-Induced Acute Kidney Injury

Abstract: Cisplatin-induced acute kidney injury is the main limiting factor restricting cisplatin’s clinical application. Accumulating evidence indicated the important role of gut microbiota in pathogenesis of acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Bioinformatic analysis as sequence alignment, operational taxonomic units (OTUs) picking, clustering, analysis of the beta diversity, and correlation analysis were performed on the Majorbio I-Sanger Cloud Platform (). 40…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatic analysis as sequence alignment, operational taxonomic units (OTUs) picking, clustering, analysis of the beta diversity, and correlation analysis were performed on the Majorbio I-Sanger Cloud Platform (). 40…”
Section: Methodsmentioning
confidence: 99%
“…A traditional Chinese formula, Zengye decoction, attenuates AKI associated with severe acute pancreatitis in rats by modulating gut microbiota. 102 Moreover, fecal microbiota transplant from donor mice treated with the Chinese medicine formula Qiong-Yu-Gao attenuated cisplatin-induced AKI in recipient mice, 103 suggesting that FMT may be an alternative treatment option for AKI. FMT may reduce the accumulation of uremic toxins in subjects with AKI, 104 as the microbial cocktail isolated from feces reduced urea and creatinine concentrations in a mice model of AKI.…”
Section: Treatmentmentioning
confidence: 99%
“…A multicenter randomized controlled clinical trial showed that Chuan Huang Fang formula combined with reduced glutathione can be used to treat AKI (1-2 grades) in CKD patients (2-4 stages) [188]. In addition, Zou et al [189] showed that intestinal flora mediates the protective effect of Qiong-Yu-Gao, a TCM formula, on cisplatin induced AKI by increasing the production of SCFA, thereby inhibiting the expression and activity of histone deacetylase, and reducing the accumulation of uremic toxins. However, it is noted that some TCMs, such as aristolochic acids and alkaloids, are deleterious to the kidney [190].…”
Section: Traditional Chinese Medicine (Tcm)mentioning
confidence: 99%